MATERNAL AND FETAL OUTCOMES IN EMERGENCY VERSUS ELECTIVE TWO OR MORE PREVIOUS CAESAREAN DELIVERIES - Rasheed, Faris A; Najim, Thikra; AL-Raheem, Yousif A (AL-Kindy College Medical Journal, 2010)
Background: Women with previous two or more caesarean deliveries are usually managed by elective cesarean section to avoid the possible risks of labor. Objective: To compare the relative risks of maternal and fetal outcomes in emergency versus elective previous two or more caesarean deliveries Design: Randomized prospective clinical study Setting: Al-Elweya Maternity Teaching Hospital, from 1st of March to 31st of September 2008. Methods: The study groups, those who had previous two or more caesarean deliveries, were included from the hospital admissions. The 1st group (102 women) presented in labor and was managed by caesarean delivery as soon as it was possible. The second group (78 women) was admitted for elective cesarean delivery. The main maternal outcomes were intra operative complications, including hysterectomy, scar dehiscence, bladder injuries, uterine and internal iliac arteries ligation, and blood transfusion. Postoperative maternal outcomes were severe morbidity including bleeding, fever, urinary tract infection, blood transfusion, the need to Intensive Care Unit admission and readmission. The fetal outcomes measures were Apgar score at one and five minutes, respiratory distress syndrome (RDS), admission to the neonatal intensive care unit and fetal loss up to hospital discharge. Results: Both groups were comparable in demographic, social and past obstetric history characteristics. Intra operative complications showed significant difference in bowel adhesions (RR 0.35, 95% CI 0.14- 0.88), and blood transfusion (RR 0.51, 95% CI 0.28- 0.94). There was statistical significant difference in the mobilization time 7.2 hours and 9.3 hours in emergency and elective groups respectively (p= 0.0009), also in feeding time, it was shorter after emergency caesarean section (P=0.0224), and in the hospital stay 24.6 and 32.6 hours respectively (p=0.0001). There was no statistical difference in post operative complications. Fetal outcomes showed no statistical significant difference in fetal loss, respiratory distress and readmission. Conclusion: Women with previous two or more caesarean deliveries can wait until starting labor for doing cesarean delivery without increasing risks to the mother and fetus.